Jewish Biblical Interpretation: Medieval and Modern Collected Essays II - Fishbane, Michael (Mohr Siebeck, 2024)
In this second collection of studies, Michael Fishbane further delves into the complex and diverse relationships between the biblical text and exegetical culture. In doing so, he emphasizes the varieties of Jewish exegetical culture, and the interplay between culture, text, and theology.
PublicationDate: 20240717
Keywords: Jewish Exegesis -- »ungodly« and »ungodly« -- 16th-century Ashkenazi literature -- synagogue liturgy -- Hebrewmanuscripts -- Hasidism -- Sabbateanism -- Jewish Theology -- Social Identity Theory (SIT) -- Social Identity Approach (SIA) -- Altes Testament -- Antike -- Jüdische Geschichte -- Religionsgeschichte des Mittelalters und der Neuzeit